Isolation of melatonin by immunoaffinity chromatography - Rolcík, Jakub; Lenobel, René; Siglerová, Vĕra; Strnad, Miroslav (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2002)
A single-step, highly specific and easy-to-use method was developed for isolation and purification of melatonin from complex biological matrices. Polyclonal antibodies highly specific against melatonin (with cross-reactivities with related compounds below 0.02%, except for 6-hydroxymelatonin) were raised, characterised by enzyme-linked immunosorbent assay (ELISA) and used for preparation of immunoaffinity gel. Melatonin recovery by the immunoaffinity method was approximately 95%, allowing single-step processing of samples prior to electrospray HPLC-MS analysis (with detection limit 10 fmol). The method was successfully used for determining melatonin in human serum and turned out to be better than the non-specific solid-phase extraction published earlier.
Keywords: hmotnostní spektrometrie s elektrosprejovou ionizací; Enzyme-Linked Immunosorbent Assay; Melatonin; Sensitivity and Specificity; chromatografie afinitní; Spectrometry, Mass, Electrospray Ionization; melatonin; zkřížené reakce; senzitivita a specificita; Cross Reactions; ELISA; Chromatography, High Pressure Liquid; Chromatography, Affinity; vysokoúčinná kapalinová chromatografie